Pengaruh Campuran Kawat Bendrat pada Karakteristik Beton dengan Subtitusi Fly Ash pada Nilai Slump - Winarko, Edy; Trimurtiningrum, Retno; Sutriono, Bantot; Rochmah, Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The increasing use of concrete in the construction world encourages massive exploitation of the environment that has limestone or karst reserves to be used as the main raw material for making cement, to reduce the excessive use of cement, a way is used to utilize fly ash as a substitute for part of the cement in the concrete mixture to reduce the negative impact of limestone mining activities as well as cement production which contributes a total of 9% of CO2 emissions on earth. In this study, bendrat wire will also be added to determine the workability of fresh concrete mixes. From the results of the study it was found that concrete with fly ash substitution without bendingt wire mixture got an average height of 10.7 cm, while the variation with the addition of bending wire at 3% decreased in the average slump value to 10 cm where the increasing percentage of bending wire made the average slump value go down, seen in the 6% and 9% variations which experienced a decrease in the average height of the slump with a height of 9.7 cm and 9 cm, this can have an impact on the workability of the concrete mix itself, with a higher percentage of bending wire will have difficulty when applying to building construction.